Alkene‐Zipper Catalyzed Selective and Remote Retro‐ene Reaction of Alkenyl Cyclopropylcarbinol. Issue 7 (13th February 2018) - Bruffaerts, Jeffrey; Vasseur, Alexandre; Marek, Ilan
Abstract: Reminiscent of biological systems, the increasingly popular concept of remote activation allows a greater strategic synthetic flexibility for the development of novel synthetic organic methodologies. In this Communication, we report that commercially available ruthenium (II)‐based "alkene zipper catalyst" enables the selective transformation of a large variety of ω‐alkenyl cyclopropylcarbinols into stereodefined unconjugated ( E )‐acyclic aldehydes bearing a quaternary stereocenter through an isomerization followed by a retro‐ene reaction. To unravel this peculiar catalytic property of the "alkene zipper" and shed some light on the mechanism, a series of control experiments were performed. Abstract :